Socio-political intentionality in communication environment of religious communities - Гриньків, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
This article analyzes the socio-political component communication environment of religious communities. The autor of article studies typical forms of communicative interaction and the author investigate differentiation of religious, social, political orientation communicative interactions religious communities.